The effect of exercise on cardiovascular risk markers in Mexican school-aged children: comparison between two structured group routines Efecto del ejercicio sobre marcadores de riesgo cardiovascular en escolares mexicanos: comparación entre dos rutinas grupales - Margie Balas-Nakash; Alejandra Benítez-Arciniega; Otilia Perichart-Perera; Roxana Valdés-Ramos; Felipe Vadillo-Ortega (Instituto Nacional de Salud Pública, 2010)
Objective. To assess the effects of two groups of exercise routines on cardiovascular disease risk markers. Material and Methods. An intervention study was conducted with 319 Mexican school-aged children in which routines were implemented Monday through Friday for 12 weeks. Routine A was the reference group, with 20 min of less intense activity and routine B was the new group with 40 min of aerobic exercises. Body mass index (BMI), waist circumference, fat mass percentage (FM%), systolic and diastolic blood pressure, lipids, lipoproteins, glucose and insulin were measured before and after the intervention. Results. Routine A had an effect on diastolic pressure, while routine B had an effect on BMI, FM%, blood pressure and triglycerides. Routine B had a greater effect on blood pressure than routine A. The prevalence of obesity, high blood pressure and hypertriglyceridemia decreased in both groups. Conclusion. Aerobic exercise is an effective health promotion strategy to reduce some cardiovascular disease risk markers. Objetivo. Evaluar el efecto de dos rutinas grupales de ejercicio sobre marcadores de riesgo cardiovascular. Material y métodos. Intervención en 319 escolares mexicanos. Las rutinas fueron implementadas por 12 semanas (rutina A (referencia): 20 min con ejercicios menos intensos vs rutina B (nueva): 40 min con ejercicios aeróbicos). Se midieron al inicio y al final el índice de masa corporal (IMC), masa grasa (%MG), presión arterial sistólica y diastólica, lípidos, lipoproteínas, glucosa e insulina. Resultados. La rutina A tuvo efecto sobre la presión diastólica; la B tuvo efecto sobre el IMC, %MG, presión arterial y triglicéridos. La rutina B tuvo mayores efectos en la presión arterial que la rutina A. Las prevalencias de obesidad, hipertensión arterial e hipertrigliceridemia disminuyeron en ambos grupos. Conclusiones. El ejercicio aeróbico es una estrategia de promoción exitosa para reducir algunos marcadores de riesgo cardiovascular.